2003
DOI: 10.1002/chin.200340237
|View full text |Cite
|
Sign up to set email alerts
|

Simple Preparation of Monodisperse Hollow Silica Particles Without Using Templates.

Abstract: plates. -The title particles are prepared by a two-step method based on the sol-gel process. In the first step Ph(MeO)3Si is hydrolyzed under acidic conditions (aq. HNO3, 60°C, 0.5-4.0 min). In the second step the condensation of the silane progresses under basic conditions (NH4OH, 1 h). The samples are characterized by SEM, TEM, and 29 Si NMR spectroscopy. The particle size and hollow diameter of the particles can be controlled by variation of the hydrolysis time. The particles are soluble in some organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 1 publication
0
36
0
Order By: Relevance
“…Liu and Chen prepared micro and nano scaled particles of silica/ fluoropolymer in tinplate to mimic the surface of lotus leaves using an emulsion mediated sol-gel process (Liu et al 2006(Liu et al , 2009. Monodisperse hollow silica particles were prepared via a two-step sol-gel method in an aqueous solution (Hah et al 2003). This process is very easy to achieve and the speed is fast.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Chen prepared micro and nano scaled particles of silica/ fluoropolymer in tinplate to mimic the surface of lotus leaves using an emulsion mediated sol-gel process (Liu et al 2006(Liu et al , 2009. Monodisperse hollow silica particles were prepared via a two-step sol-gel method in an aqueous solution (Hah et al 2003). This process is very easy to achieve and the speed is fast.…”
Section: Introductionmentioning
confidence: 99%
“…For example, H. J. Hah and coworkers 120) have prepared hollow SiO 2 particles without using templates. Their preparation procedure included two steps.…”
Section: In-situ Product Template Methodsmentioning
confidence: 99%
“…The metal templates are removed by selective dissolution or sublimation after the formation of solid shell. For example, Z. Wang and co-workers 117) [120][121][122][123][124] have reported that they have prepared hollow particles without using templates. Actually, even they did not add template .…”
Section: In-situ Product Template Methodsmentioning
confidence: 99%
“…The design and synthesis of hollow nanostructure have been of great interest in the past decades [1][2][3][4][5]. Among which hollow silica nanospheres (HSNSs) have attracted tremendous interest due to their fascinating properties, such as excellent mechanical and thermal stability, favorable biocompatibility, large surface area and pore volume, low toxicity and permeable porous shell [2,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%